(untitled) (International Journal of Food and Nutritional Sciences, 2024)
Fake Product Review Monitoring and Evaluation aims to enhance the authenticity of online product reviews by detecting and eliminating fake reviews. Users can log in to a shopping platform, purchase products, and leave reviews only for items they have bought, ensuring that reviews come from verified buyers. Admins can manage the platform, monitor reviews, and identify fake ones by analysing user IP addresses, the sentiment of reviews, and their relevance. By employing data mining and opinion mining techniques, the system ensures that only genuine, trustworthy reviews remain, improving consumer trust and promoting fair competition.